FC 129: Stopping versus Continuing Renin–Angiotensin System Inhibitors After Acute Kidney Injury and Adverse Clinical Outcomes: An Observational Study From Routine Care Data. (3rd May 2022) - Janse, Roemer; Fu, Edouard; Clase, Catherine M; Tomlinson, Laurie; Lindholm, Bengt; Van Diepen, Merel; Dekker, Friedo W; Jesus Carrero, Juan
Abstract: BACKGROUND AND AIMS: The risk–benefit ratio of continuing with renin–angiotensin system inhibitors (RASi) after an episode of acute kidney injury (AKI) is unclear. While stopping RASi may prevent recurrent AKI or hyperkalaemia, it may deprive patients of the cardiovascular benefits of using RASi. METHOD: We analysed outcomes of long-term RASi users experiencing AKI (stage 2 or 3, or clinically coded) during hospitalization in Stockholm, Sweden, during 2007–2018. We compared stopping RASi within 3 months after discharge with continuing. The primary study outcome was the composite of all-cause mortality, myocardial infarction and stroke. Recurrent AKI was our secondary outcome, and we considered hyperkalaemia as a positive control outcome. Propensity score overlap weighted Cox models were used to estimate hazard ratios, balancing 75 confounders. Weighted absolute risk differences (ARD) were also determined. RESULTS: We included 10 165 individuals, of whom 4429 stopped and 5736 continued RASi, with a median follow-up of 2.3 years. Median age was 78 years, 45% were women, and median kidney function before the index episode of AKI was 55 mL/min/1.73 m 2 . After weighting, those who stopped had an increased risk [HR, 95% confidence interval (95% CI)] of the composite of death, myocardial infarction and stroke (1.13, 1.07–1.19; ARD 3.7, 95% CI 2.6–4.8) compared with those who continued, a similar risk of recurrent AKI (0.94, 0.84–1.05), and a decreased risk of hyperkalaemia (0.79, 0.71–0.88). CONCLUSION: Stopping RASi use among survivors of moderate-to-severe AKI was associated with a similar risk of recurrent AKI, but higher risk of the composite of death, myocardial infarction and stroke.